2014
DOI: 10.1002/meet.2014.14505101059
|View full text |Cite
|
Sign up to set email alerts
|

File synchronization and sharing: User practices and challenges

Abstract: In this paper, we present results of qualitative analysis of interviews with 16 university faculty regarding their use of file synchronization and sharing technologies in their work and personal lives. We identify key problems and considerations that influence file synchronization and sharing practices, and describe commonly used strategies. Our findings show that while behaviors have evolved as technology changes, users continue to make extensive use of familiar patterns of access, including automated and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Users' files come from various sources, including the web (Huvila, Eriksen, Häusner, & Jansson, 2014;Jones, Bruce, & Dumais, 2001), external devices (Capra, Vardell, & Brennan, 2014), and peer-to-peer or cloud software (Marshall & Tang, 2012), although do not often come from their cell phones, despite the ability to download files to smart phones from the web (Capra, 2009). Several studies have sought to understand the contents of users' collections, finding, for example, that document and image files are the most common types kept by students and knowledge workers (GonQalves & Jorge, 2003;Hicks et al, 2008), and that files may be regarded by users as ephemeral, archived, or current for their intended use (Nardi, Anderson, & Erickson, 1995).…”
Section: Understanding User Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Users' files come from various sources, including the web (Huvila, Eriksen, Häusner, & Jansson, 2014;Jones, Bruce, & Dumais, 2001), external devices (Capra, Vardell, & Brennan, 2014), and peer-to-peer or cloud software (Marshall & Tang, 2012), although do not often come from their cell phones, despite the ability to download files to smart phones from the web (Capra, 2009). Several studies have sought to understand the contents of users' collections, finding, for example, that document and image files are the most common types kept by students and knowledge workers (GonQalves & Jorge, 2003;Hicks et al, 2008), and that files may be regarded by users as ephemeral, archived, or current for their intended use (Nardi, Anderson, & Erickson, 1995).…”
Section: Understanding User Behaviormentioning
confidence: 99%
“…When backing up their files, people may rely on dedicated backup, sharing, or syncing services such as Dropbox or Apple's Time Capsule to make their backups (Marshall & Tang, ). However, some people feel these methods are not reliable or do not fit well into their schedules or operations, and so may initiate and make backups manually (Capra et al, ; Dearman & Pierce, ), for example as a consequence of related activities (Kljun, Mariani, & Dix, ). Not all users make backups (Kljun et al, ), but may nonetheless feel that they should be doing so or doing so more frequently (Kearns, Frey, Tomer, & Alman, ).…”
Section: Motivations Of File Management Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal content sharing may be embedded in activities or applications used for two, often interrelated, tasks: personal information management, or "personally organizing" one's files, for example for synchronization across devices, and group information management, managing files in a collaborative setting such as a repository system (e.g., Dropbox, Google Drive) [1]. To choose channels for information management, users tend to consider content size, privacy and security, institutional policy, service accessibility and usability, and group familiarity with systems [4,30,32]. For example, when choosing between cloud storage and email for file management, people tended to choose email for its perceived reliability, simplicity, broad access, and level of control.…”
Section: Information Managementmentioning
confidence: 99%
“…be assigned to others. This distinction is not always intuitive to users, who require more explanation of how file sharing works [15]. Early user experiences with the cloud revealed that users needed to understand a variety of cloud functions, including replication and synchronization, in order to make full use of cloud storage [33].…”
Section: Retrospective Privacy Of Social Mediamentioning
confidence: 99%